Comparison of some physical abilities between female students for the morning and evening studies in the College of Basic Education. A descriptive research on female students of the first stage in the Department of Physical Education.pdf (Journal of the College of Basic Education, 2023)
The British presence in the Arabian Gulf was exposed to competition from other European powers.And since an early stop, led by the Portuguese, the Dutch and the French, Britain was ableThrough a long political and military struggle that lasted nearly three centuries, it got rid of its competition.European powers, but that does not mean an end to the troubles that faced Britain, as soonThe Russian penetration appeared clearly and posed a threat to British interests in the ninth century.Tenth, following the entry of Russian ships into the waters of the Arabian Gulf and their frequenting of ports and citiesthe eastern and western coasts.